A case report on autoimmune polyglandular syndrome type 2 with pernicious anemia - Niharikha Arram; Romana Riyaz; Sumalatha khatroth; Abhigan Babu Shrestha (Clinical Case Reports, 2023)
Abstract Autoimmune polyglandular syndrome type 2 (APS II) is a rare autoimmune disease that affects many endocrine glands. We present a case of a 32‐year‐old man with Addison's disease, autoimmune thyroiditis, and pernicious anemia. Multi‐line and timely management are crucial for each association.